MODELING THE WATER LEVEL REGIME OF LAKE ARPI (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The work is devoted to modeling the level regime of the Arpi Lake-reservoir. The multiple linear regression apparatus is used, with the help of step-by-step exclusion of predictors, a statistically adequate and physically justified model is selected. The article describes the possibility of replacing atmospheric precipitation as a function of the influence on the water level with indirect factors such as relative air humidity. The model is derived from standardized data with monthly discreteness, an assessment of the model's effectiveness is given on dependent and independent material.
Keywords: Lake Arpi; water level regime; regression analysis; air humidity; probabilistic model